Expanding the Clinical Spectrum of Osteogenesis Imperfecta Type V: 13 Additional Patients and Review - Cao, Yang-Jia; Wei, Zhe; Zhang, Hao; Zhang, Zhen-Lin (Frontiers in Endocrinology, 2019)
Osteogenesis imperfecta (OI) is an inherited connective tissue disorder characterized by bone fragility and is characterized by clinical and genetic heterogeneity. Previous studies showed that the same mutation (c.–14C>T) of the IFITM5 gene is responsible for autosomal dominant OI type V. However, the mutation has a variable expressivity. Clinical heterogeneity has been recognized in OI type 5. In this study, we investigated 13 individuals with molecularly confirmed OI type 5 from 7 Chinese families and explored the genotype-phenotype relationship. Increased callus formation is not observed in all individuals, and several novel clinical features were described: joint contractures (3 individuals) and unexplained hip arthritis (6 individuals). Significant clinical variability was observed even within families. Specific facial features were observed in 6 individuals from 2 families consistent with the facial features associated with OI type 5 reported so far in the literature. Interestingly, we report the process of hypertrophic callus formation in detail for the first time, and in 5 individuals with hyperplastic callus, increased erythrocyte sedimentation rate (ESR) and levels of C-reactive protein (C-RP) were measured, suggestive of inflammatory activation.